PENGARUH SUPLEMENTASI ASAM AMINO LISIN PADA PAKAN DENGAN DOSIS YANG BERBEDA TERHADAP KELANGSUNGAN HIDUP DAN PERTUMBUHAN BENIH IKAN GURAMI (Osphronemus goramy) - Ardiansyah, Nur; Ma'ruf, Mohamad; Isriansyah, Isriansyah; Mubin, Ahmad Fatkhul (Program Studi Budidaya Perairan, Fakultas Pertanian, Universitas Sriwijaya, 2024)
This study aimed to analyze the effect of amino acid lysine supplementation to artificial feed on survival rate and growth of giant gourami fry (Osphronemus goramy), and to determine the optimal lysine dose for giant gourami fry. This study was carried out for 60 days. The experiment using the Completely Randomized Design (CRD) method with 4 treatments and 3 replications. The Treatment used 0%, 1%, 2%, and 3% lysine addition on artificial feed. The Results of this study show that the lysine addition on artificial feed significantly influence on absolute weight growth and specific growth rate (P<0.05), however not significantly influence on survival rate and total length growth of giant gourami fry (P>0.05). P3 (2% lysine) gave the highest average value on absolute weight growth (42,91 g), specific growth rate (3,80%/day), and total length growth (7,13 cm). The Water quality parameter values during this study still suitable to support the survival and growth gourami fry with 100% survival rate on each treatment. Key words : Giant Gouramy (Osphronemus goramy), Amino Acid Lysine Supplementation, Survival rate, Growth.